Diabetes Mellitus as a Risk Factor for Development of Depressive Symptoms in a Population‐Based Cohort of Older Mexican Americans. Issue 3 (March 2016) - Garcia, Maria E.; Lee, Anne; Neuhaus, John; Gonzalez, Hector; To, Tu My; Haan, Mary N.
Abstract : Objectives: To determine whether diabetes mellitus increases depressive symptoms in older Latinos in a population‐based cohort. Design: Prospective cohort study. Participants: Individuals from the Sacramento Latino Study on Aging aged 60 and older in 1998–99 and followed annually until 2008 (N = 1, 586). Measurements: Diabetes mellitus was defined according to self‐report, fasting blood glucose of 126 mg/dL or greater, glycosylated hemoglobin of 6.5% or greater, or diabetic medication use. Depressive symptoms were defined as Center for Epidemiologic Studies Depression Scale (CES‐D) score of 16 or greater or use of antidepressant medication. Multistate Markov modeling was used to assess the effects of time‐dependent diabetes mellitus on transitions between three states over time: low CES‐D score (normal), high CES‐D score or treated (depressed), and death. Bivariate analyses identified covariates significantly associated with any transition, including sex and baseline measures of age, education, body mass index, hypertension, and stroke. Results: In a fully adjusted model, participants with diabetes mellitus had a 35% higher rate of developing depressive symptoms or starting treatment with an antidepressant (hazard ratio (HR) = 1.35, 95% confidence interval (CI) = 1.13–1.62). Time‐dependent diabetes mellitus was associated with a lower rate of regression from depressed to normal (HR = 0.72, 95% CI = 0.59–0.88) and a 2.3 greater rate pf progression from depressed to death (HR = 2.31, 95% CI = 1.57–3.40). Conclusion: Diabetes mellitus increased the risk of developing depressive symptoms in older Mexican Americans. Older Latinos with diabetes mellitus should be screened for depressive symptoms and prioritized for close follow‐up, potentially through greater reliance on team‐based models of care.